Persepsi guru mata pelajaran sejarah tentang implementasi Kurikulum Merdeka di SMAN 1 Kedunggalar Kabupaten Ngawi - Aji, Meru Pangesthi; Widiadi, Aditya Nugroho (Historiography: Journal of Indonesian History and Education, 2024)
Abstract As a new policy, the implementation of the Merdeka Curriculum cannot be separated from the pros and cons among teachers. Including among history teachers at SMAN 1 Kedunggalar, Ngawi Regency, which is still in the process of adjusting from the 2013 Curriculum to the Merdeka Curriculum. This study uses a qualitative approach in order to understand the problems studied based on the participants' perspectives, in this case, the perceptions of history subject teachers regarding the Merdeka Curriculum and how it is implemented in history learning. The results of this study indicate that the Implementation of Merdeka Curriculum at SMA Negeri 1 Kedunggalar has provided positive benefits for educators and students through new learning models such as Project Based Learning (PJBL) which are considered capable of increasing learning enthusiasm, creativity, and student involvement. The Strengthening the Pancasila Student Profile (P5) program is also considered to have a positive impact in shaping student character in accordance with the values of Pancasila. However, there are shortcomings related to the lack of history lesson time due to difficulties in managing time between the P5 program and history materials. Therefore, it is hoped that there will be further socialization and training on Merdeka Curriculum at SMA Negeri 1 Kedunggalar.Abstrak Sebagai sebuah kebijakan baru, implementasi Kurikulum Merdeka tidak bisa lepas dari pro-kontra di kalangan para guru. Termasuk diantara para guru sejarah di SMAN 1 Kedunggalar Kabupaten Ngawi yang masih proses penyesuaian dari Kurikulum 2013 ke Kurikulum Merdeka. Penelitian ini menggunakan pendekatan kualitatif agar dapat memahami masalah-masalah yang dikaji berdasar perspektif partisipan, dalam hal ini adalah persepsi guru mata pelajaran sejarah mengenai Kurikulum Merdeka dan bagaimana pengimplentasiannya dalam pembelajaran sejarah. Hasil dari kajian ini menunjukkan bahwa Implementasi Kurikulum Merdeka di SMA Negeri 1 Kedunggalar telah memberikan manfaat positif bagi pendidik dan siswa melalui model pembelajaran baru seperti Project Based Learning (PJBL) yang dianggap mampu meningkatkan semangat belajar, kreativitas, dan keterlibatan siswa. Program Penguatan Profil Pelajar Pancasila (P5) juga dianggap berdampak positif dalam membentuk karakter siswa sesuai dengan nilai-nilai Pancasila. Namun, ada kekurangan terkait kurangnya waktu pelajaran sejarah karena kesulitan dalam pengaturan waktu antara program P5 dan materi sejarah. Oleh karena itu, diharapkan adanya sosialisasi dan pelatihan lebih lanjut tentang Kurikulum Merdeka di SMA Negeri 1 Kedunggalar.